MEMBANGUN LAYANAN INFORMASI PERUNDANG-UNDANGAN MENGGUNAKAN INSTANT MESSENGER (Information Technology and Telematics, 2014)
Abstract - The law is a set of written rules made ​​by government and binding. Legislation should become familiar among the public for the purpose of these laws can be realized. Communication over the internet is one good alternative ntuk promote laws. This research will make the system services legislation menggungakan instant messenger. The goal is to facilitate the public to get information about the legislation is broad and deep. Instant Messenger is a form of short message communication between two or more people using typed text. This system will be used by the public to access data legislation by typing a query as input, and then the system will display the appropriate legislation query the data is entered as the output. Web services uses Instant Messenger legislation was created using the Java programming language with the help of Netbeans IDE 7.0. As for the database used is Microsoft SQL Server 2008 R2. This study resulted in a medium that allows people to access data with a database of legislation in the form of XML documents. Keywords: XML, Java, SQL Server, legislation Abstrak - Undang-undang adalah kumpulan peraturan tertulis yang dibuat oleh pemerintah dan bersifat mengikat. Seyogyanya undang- undang menjadi hal yang familiar di kalangan masyarakat agar tujuan dari undang- undang tersebut dapat terealisasi. Komunikasi melalui internet adalah salah satu alternatif yang baik ntuk memasyarakatkan undang- undang. Penelitian ini akan membuat sistem layanan perundang- undangan menggunakan instant messenger sehingga menghasilkan sebuah media yang memudahkan masyarakat untuk mengakses data perundang- undangan dengan basis data dokumen dalam bentuk xml. Instant Messenger adalah bentuk komunikasi pesan singkat antara dua orang atau lebih menggunakan teks yang diketik. Sistem ini akan digunakan oleh masyarakat untuk mengakses data perundang- undangan dengan mengetikkan query sebagai masukan (input), dan kemudian sistem akan menampilkan data perundangan sesuai query yang diinputkan sebagai keluaran (output).Kata Kunci : XML, Java, SQL Server, Perundang-Undangan